Translational strategy: humanized mini-organs. Issue 11 (November 2018) - Nguyen, Duong T.; Althage, Magnus; Magnone, Maria Chiara; Heydarkhan-Hagvall, Sepideh
Highlights: Translational research helps to develop humanized micro-physiological systems. Decellularized and recellularized organs have preserved vascular matrix network. The mini-organs can be a platform for disease modeling for precision medicine. Humanized organs can be co-cultured to model systemic drug uptake. Humanized mini-organs can provide human-relevant evidence of target engagement. Abstract : Mini-organs engineered from decellularized organs repopulated with human stem cells can transform preclinical model strategies in target validation and biomarker discovery. Recellularized organs are whole humanized organs with preserved native architecture, conformity of the organ, composition of extracellular matrix and vascular matrix structures. With mini-organ models further understanding of developmental biology and assessment of potential therapeutic targets can be elucidated utilizing human induced pluripotent stem cells. As a next step, co-cultured mini-organ models could simulate pharmacokinetics and pharmacodynamics in physiological and pathological conditions. By overcoming key challenges, the development of humanized mini-organs as integrated biotechnology can address the translational gaps between in vitro, ex vivo and in vivo systems for an elevated human target validation model.